Evaluation of cost-effectiveness of live oral pentavalent reassortant rotavirus vaccine introduction in Ghana - Abbott, C.; Tiede, B.; Armah, G.; Mahmoud, A. (Vaccine, 2012)
Background: Globally, rotavirus gastroenteritis is the most common identifiable cause of severe diarrhea in children under 5. Recently introduced rotavirus vaccines from Merck & Co. and GlaxoSmithKline have the potential to save hundreds of thousands of lives. Efficacy results in Ghana suggest Merck & Co.'s live oral pentavalent rotavirus vaccine (RotaTeq ®) prevents 65.0% of severe gastroenteritis due to rotavirus infection in children under 5. The announcement by Merck and GSK to make their rotavirus vaccines available for developing nations at reduced prices provides Ghana with the opportunity to introduce rotavirus vaccines into the national immunization program after investigation of the medical, economic and political implications. Methods: We estimated the average costs of treating children with diarrhea in the Ashanti region of Ghana as inpatients and outpatients. Using these results, data from rotavirus surveillance studies, and recent rotavirus vaccine efficacy evaluation, we estimated the cost-effectiveness of introducing RotaTeq in Ghana. Results: Based on our prospective calculations, we estimated an average inpatient and outpatient costs of $233.97 and $17.09, respectively, for treating childhood diarrhea. Using the 2003 birth cohort, RotaTeq introduction could save 1554 lives and avert 93,109 disability-adjusted life-years (DALYs) annually. At a market price of $5 per dose, introducing RotaTeq would have a base-case cost of $62.26 per DALY averted, at a market price of $3.50 per dose, a base-case cost of $39.59 per DALY averted and at market cost of $1 per dose, a base-case cost of $1.81 per DALY averted. All three values are below the 2009 Ghana per capita GDP. Thus, RotaTeq introduction into Ghana will be very cost-effective. Sensitivity analyses suggest these results are robust. Conclusions: RotaTeq vaccination for children under five in Ghana would be a highly cost-effective public health intervention. Ghanaian health officials should seek GAVI funding and evaluate how to maximize RotaTeq access. © 2012 Elsevier Ltd.
Keywords: Cost-effectiveness; Ghana; Rotavirus vaccine